Alter Design: A clearing where design is revealed as coming full circle to its forgotten origins and dissolved into nondesign. Issue 1 (2nd January 2017) - López-Garay, Hernán; Molano, Daniel Lopera
Abstract: Design for/by the Global South is a field that begins to show itself as constituted by a dialectical tension between design and alter design . The latter is a historical clearing where design is revealed as coming full circle from its forgotten origins (which were in the transformation of tékhne into technique) to finally dissolve itself into non-design . Cultivating the recovery of this memory and beginning to display the aforementioned dialectics is of vital importance for the future of humankind, since design is highly implicated in the unfolding of a world order that has become totally unsustainable.